An Analysis of the Determinants of Informal Employment in Urban and Rural Regions in Iran: Pseudo-Panel Data Approach - Shahryar Zaroki; Mastaneh Yadollahi Otaghsara; Arman Yousefi Barfurushi (فصلنامه پژوهش‌های اقتصادی ایران, 2021)
Informal employment typically poses many problems for communities and governments. For example, most informal workers face problems relating to poverty and economic insecurity due to the lack of a social security organization and labor law in the informal sector. Informal employment also has detrimental effects on governments, such as incorrect estimates of GDP and tax cuts. Accordingly, identifying the factors affecting informal employment will greatly help economic policymakers to control this phenomenon. This study attempts to examine the determinants of informal employment in urban and rural areas of Iran between 2013 and 2019. To this aim, applying the urban and rural household income-expenditure survey in the mentioned period, the share of informal employment in the total employment was calculated. Preliminary data processing illustrates that, on average, 45.1% of urban employees and 74.6% of rural employees are engaged in informal occupations. The results of estimating the research model indicate that employees' level of education and marital status have an indirect (favorable) effect on informal employment in urban and rural areas. There is also a U-shaped relationship between age and informal employment. At the same time, being a man in urban areas and being a woman in rural areas increase informal employment.